Mycobacterium tuberculosis spoligotypes and drug susceptibility pattern of isolates from tuberculosis patients in South-Western Uganda - Bazira, Joel (BioMed Central, 2011)
BACKGROUND: Determination of the prevalence and drug susceptibility of the M. tuberculosis strains is important in tuberculosis control. We determined the genetic diversity and susceptibility profiles of mycobacteria isolated from tuberculosis patients in Mbarara, South Western Uganda. METHODS: We enrolled, consecutively; all newly diagnosed and previously treated smear-positive TB patients aged ≥ 18 years. The isolates were characterized using regions of difference (RD) analysis and spoligotyping. Drug resistance against rifampicin and isoniazid were tested using the Genotype(® )MDRTBplus assay and the indirect proportion method on Lowenstein-Jensen media. HIV-1 testing was performed using two rapid HIV tests. RESULTS: A total of 125 isolates from 167 TB suspects (60% males) with a mean age 33.7 years and HIV prevalence of 67.9% (55/81) were analyzed. Majority (92.8%) were new cases while only 7.2% were retreatment cases. All the 125 isolates were identified as M. tuberculosis strict sense with the majority (92.8%) of the isolates being modern strains while seven (7.2%) isolates were ancestral strains. Spoligotyping revealed 79 spoligotype patterns, with an overall diversity of 63.2%. Sixty two (49.6%) of the isolates formed 16 clusters consisting of 2-15 isolates each. A majority (59.2%) of the isolates belong to the Uganda genotype group of strains. The major shared spoligotypes in our sample were SIT 135 (T2-Uganda) with 15 isolates and SIT 128 (T2) with 3 isolates. Sixty nine (87%) of the 79 patterns had not yet been defined in the SpolDB4.0.database. Resistance mutations to either RIF or INH were detected in 6.4% of the isolates. Multidrug resistance, INH and RIF resistance was 1.6%, 3.2% and 4.8%, respectively. The rpoβ gene mutations seen in the sample were D516V, S531L, H526Y H526D and D516V, while one strain had a Δ1 mutation in the wild type probes. There were three strains with katG (codon 315) gene mutations only while one strain showed the inhA promoter gene mutation. CONCLUSION: The present study shows that the TB epidemic in Mbarara is caused by modern M. tuberculosis strains mainly belonging to the Uganda genotype and anti-TB drug resistance rate in the region is low.